Evaluation of arbuscular mycorrhizal fungi against Macrophomina phaseolina causing dry root-rot of urd and mung bean - and H.K. KEHRI*, SUDHIR CHANDRA, VARUN KHARE (Indian Phytopathology, 2007)
Macrophomina phaseolina (Tassi.) Goid., a soil-borne pathogen, causes serious diseases of diverse crops in India hampering their yield. Conventional methods to check these diseases are difficult becauseof the predominantly subterranean habit and strong competitive ability of the pathogen. AM fungi have potential to negate the activity of a number of soil-borne pathogens. Plants inoculated with AM symbiont exhibit an increased resistance to fungal root diseases. Therefore, a number of AM fungi viz., Glomus fasciculatum, G. mosseae, G. aggregatum, G. claroideum, G. macrocarpum, and G. multicaule were evaluated to check M. phaseolina causing dry root-rot of mungbean (Vigna radiata (L.) Wilczek.), var. T-44 and Pusa Baisakhi, as well as urdbean (Vigna mungo (L.) Hepper), var. T-9 and Bhadeli. G. claroideum was found to be a better biocontrol agent for mungbean var. T-44, while G. mosseae for var, Pusa Baisakhi. G. aggregatum proved to be a potent biocontrol agent for both the varieties of urdbean. The findings suggest that the AM fungi might be used as the biocontrol agent since they have the potentiality to nullify the damaging effect of the pathogen.